Keputusan Pendanaan,Kebijakan Deviden dan Agresivitas Pajak - Alfiana Zunita; Batara Daniel Bagana (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of Funding Decisions, Dividend Policy and Tax Aggressiveness on Firm Value.Population in this study is the property and real estate sector companies listed on the IDX in 2015-2019. The sample companies obtained and meet the criteria are 9 companies and the data that can be processed is 45 annual report data. The data analysis used is descriptive statistics, classical assumption test, multiple linear regression, and hypothesis testing using SPSS version 21.0 program. The results of the partial test (t test), Funding Decisions have a significant positive effect on Firm Value, Dividend Policy has a significant positive effect on Firm Value, while Tax Aggressiveness has no effect on Firm Value.